Potential implications of ’Farm Laws 2020’ on rice marketing in India: A discussion - Mondal, Biswajit; Bisen, Jaiprakash; Kumar, Suresh; Majumder, Saddam Hossen; Mishra, S K; Kumar, GAK; Sinha, M K; Tiwari, Utkarsh; Punia, Meenu (ORYZA-An International Journal of Rice, 2021)
The new farm laws remain a contentious issue in the political debates and discussions from their enactment.Â Protests are being organised across the country for their repeal. Rice is an important crop, produced andÂ consumed by almost every farmer in India. Hence, the issue lodges an important place in the agriculture canvasÂ of the country. In this context, this articles makes the first attempts to discuss the commodity-specific implicationsÂ of these laws. In this article, we have provided an elaborate view on the three farm laws enacted in the year 2020Â namely (1) The Farmers’ Produce Trade and Commerce (Promotion and Facilitation) Act, 2020; (2) FarmersÂ (Empowerment and Protection) Agreement on Price Assurance and Farm Services Act, 2020; and (3) EssentialÂ Commodities (Amendment) Act, 2020 and discussed their possible implications on rice marketing in India.